PETROLEUM CHARACTERISTICS ETER AND DIETIL ETER AS THE WORK ENERGY WATER ENERGY PUMP - F.A. Rusdi Sambada; A. Prasetyadi (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2014)
Water pumps in areas without electricity are generally driven by fuel engine. The problem arises while the fuel is getting scarce and expensive. This research aims to create a model of thermal energy water pump and examine petroleum ether and diethyl ether characteristics as working fluid of thermal energy water pump. Parameter variations are done on type of fluid, mass of the working fluid and pumping head. Measurements are conducted on temperature of the working fluid, pumping discharge, time, working fluid pressure and pump pressure. A cycle time of petroleum ether is 158 minutes which is 6 times longer than diethyl ether (24.3 minutes). The discharges of diethyl ether are 0.9, 0.7 and 1.3 liters/min in average, minimum and maximum respectively. They are greater than petroleum ether (0.3, 0.1 and 1.1 liters/min). Diethyl ether generated evaporator pressure greater than petroleum ether (0.7 vs. 0.55 bar). Amount of air in the pressured air tube and in the system affects the volume and discharge. There is optimal mass of working fluid for specific head and amount of air in the pressured air tube. There is also optimal head for specific amount of working fluid mass and air in the pressured air tube.